Flexible Devices: Ultrastretchable Kirigami Bioprobes (Adv. Healthcare Mater. 3/2018). Issue 3 (7th February 2018) - Morikawa, Yusuke; Yamagiwa, Shota; Sawahata, Hirohito; Numano, Rika; Koida, Kowa; Ishida, Makoto; Kawano, Takeshi
Abstract : The most remarkable features of Kirigami are that unstretchable materials can gain stretchability and that its strain force is very small compared to other elastomer‐based stretchable materials. These features are suitable for applications related to deformable soft biological samples. In article number1701100, Takeshi Kawano and co‐workers propose the ultrastretchable bioprobe device using a 'Kirigami' design and demonstrate the recordings of biological signals in mouse brain and heart.